Suspected Child Abuse and Neglect Team (SCAN Team): early establishment, success stories, challenges and the way forward / Yarina Ahmad ... [et al.] - Ahmad, Yarina; Denise, Cuthbert; Arunachalam, Dharma; Niner, Sara (Faculty of Administrative Science and Policy Studies, 2015)
This paper presents a pioneering program/initiative to prevent child abuse in Malaysia: Suspected Child Abuse and Neglect Team (hereafter SCAN Team). While there are three main initiative/programs to prevent child abuse in Malaysia, namely Child Protection Team, Child Protection Unit and SCAN Team; this paper focuses on only one initiative – SCAN Team which based at the General Hospital Kuala Lumpur (hereafter GHKL). The presentation of this paper is based on the findings of in-depth interview with focal person who manages SCAN Team, and further supported by relevant important documents related to SCAN Team (i.e. archives newspaper from SCAN Team, Malaysian Social Institute (Institut Sosial Malaysia – ISM) and relevant secondary data). Findings of this study revealed that SCAN Team has effectively deal with challenges during its early establishment; notably, SCAN Team has received international recognition in 1998 for ‘protecting the lives of children’. Nonetheless, the awareness of public about the existence of SCAN Team has waned in 21st Century due to several issues and challenges. Despite this, SCAN Team is moving forward through initiatives, in particular, re-marketing their program through various activities and campaigns to prevent child abuse in Malaysia.